2020
DOI: 10.1002/csc2.20345
|View full text |Cite
|
Sign up to set email alerts
|

Identification and diversity of tropical maize inbred lines with resistance to common rust (Puccinia sorghi Schwein)

Abstract: Common rust (CR) caused by Puccinia sorghi Schwein is one of the major foliar diseases of maize (Zea mays L.) in Eastern and Southern Africa. This study was conducted to (i) evaluate the response of elite tropical adapted maize inbred lines to Puccinia sorghi and identify resistant lines (ii) examine associations between CR disease parameters and agronomic traits, and (iii) assess the genetic diversity of the inbred lines. Fifty inbred lines were evaluated in field trials for three seasons (2017–2019) in Ugand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 78 publications
(132 reference statements)
0
5
0
Order By: Relevance
“…In this study, highly susceptible Pima S-7 had the highest regression coefficients on each planting date, while FM 2334 RF had the lowest regression coefficients on two planting dates (5/7 and 6/17), and PHY 725 RF and Pima PHY 881 RF had similar and intermediate regression coefficients. Thus, the regression coefficient (slope) can be used to compare levels of resistance among different cotton germplasm lines instead of using DSR or MR at only one-time point, in addition to the area under the disease progress curve (AUDPC) that is used to quantitatively summarize disease severity over time, for comparison among cultivars (Simko and Piepho, 2012 ; Fernández-Campos et al, 2020 ; Serumaga et al, 2020 ; Zhu et al, 2021a , b ). Fernández-Campos et al ( 2020 ) recently showed that logistic models (polycyclic) provided the best fitting disease progress curve in all eight tested wheat cultivars against the wheat blast disease, which was followed by the Gompertz model; however, epidemiological parameters differed between genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, highly susceptible Pima S-7 had the highest regression coefficients on each planting date, while FM 2334 RF had the lowest regression coefficients on two planting dates (5/7 and 6/17), and PHY 725 RF and Pima PHY 881 RF had similar and intermediate regression coefficients. Thus, the regression coefficient (slope) can be used to compare levels of resistance among different cotton germplasm lines instead of using DSR or MR at only one-time point, in addition to the area under the disease progress curve (AUDPC) that is used to quantitatively summarize disease severity over time, for comparison among cultivars (Simko and Piepho, 2012 ; Fernández-Campos et al, 2020 ; Serumaga et al, 2020 ; Zhu et al, 2021a , b ). Fernández-Campos et al ( 2020 ) recently showed that logistic models (polycyclic) provided the best fitting disease progress curve in all eight tested wheat cultivars against the wheat blast disease, which was followed by the Gompertz model; however, epidemiological parameters differed between genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, Sserumaga et al. (2020) studied tropical maize lines with resistance to common rust ( Puccinia sorghi Schwein) evaluated in Uganda. They also assessed the genetic diversity and population structure within these lines.…”
Section: The Importance Of Plant Healthmentioning
confidence: 99%
“…Common rust (CR) in maize ( Zea mays L. ), caused by an obligate fungal pathogen Puccinia sorghi Schwein, is one of the most pervasive diseases in many maize-growing regions ( Sserumaga et al, 2020 ), and yield losses of up to 49% were reported in susceptible germplasm ( Groth et al, 1983 ). Because of the severity of the disease, several authors have investigated the genetic basis of resistance to CR and have identified different quantitative trait loci (QTL) ( Kerns et al, 1999 , Danson et al, 2008 , Zheng et al, 2018 , Ren et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%